Consumer Attitudes Towards Domestic Solar Power Systems - Faiers, Adam; Neame, Charles (Elsevier, 2006)
The success of the UK policy to reduce carbon emissions is partly dependent on the ability to persuade householders to become more energy efficient, and to encourage installation of domestic solar systems. Solar power is an innovation in the UK but the current policy of stimulating the market with grants is not resulting in widespread adoption. This case study, using householders in central England, investigates householder attitudes towards characteristics of solar systems and identifies some of the barriers to adoption. The study utilises Diffusion of Innovations theory to identify attitudes towards system attributes, and isolates the characteristics that are preventing a pragmatic ‘early majority’ from adopting the technology. A group of ‘early adopters’, and a group of assumed ‘early majority’ adopters of solar power were surveyed and the results show that overall, although the ‘early majority’ demonstrate a positive perception of the environmental characteristics of solar power, its financial, economic and aesthetic characteristics are limiting adoption. Differences exist between the two groups showing support for the concept of a ‘chasm’ between adopter categories after Moore (Crossing the Chasm: Marketing and Selling High-tech Products to Mainstream Customers, second ed. Harper Perennial, New York). However, if consumers cannot identify the relative advantage of solar power over their current sources of power, which is supplied readily and cheaply through a mains system, it is unlikely that adoption will follow. Recommendations concerning the marketing and development of solar products are identified.
Keywords: Solar Power; Innovation Adoption; Consumer Perceptions